Abordagem sobre as práticas de higiene íntima feminina em uma unidade básica de saúde no município de Altamira - PA: relato de experiência - CORDEIRO, Elizandra Nogueira (2024)
Introduction: The lack of information about care for the female intimate region is still considered a taboo in our current society. Daily feminine intimate hygiene is of paramount importance for the prevention of infections and for the well-being of women. However, it is perceived that there is still a lack of knowledge on the part of women when approaching this topic. Objective: The objective is to report the experience in educational actions on female intimate hygiene practices in a UBS in the city of Altamira, seeking to expand access to information from users and thus evaluate the level of knowledge of women about the importance of self-care. Methodology: This is a study of the health education type, with the target audience being women who attend the Basic Health Unit selected in the city of Altamira-PA, more precisely with the UBS of Brasília, in the Brasília neighborhood as the place of application. where health actions will be developed with the aid of illustrative banners, educational folders and lectures that will be given in simple and objective language, on the content addressed in the educational intervention. The present work will serve as a tool to broaden the understanding of the adoption of self-care as a preventive measure, promoting awareness and health promotion. The esplanade theme is favorable since women routinely seek health services for consultations that involve their self-care, making the dissemination of information valid.